Highly Ordered BN⊥–BN⊥ Stacking Structure for Improved Thermally Conductive Polymer Composites. (8th October 2020) - Ghosh, Barun; Xu, Fang; Grant, David M.; Giangrande, Paolo; Gerada, Chris; George, Michael W.; Hou, Xianghui
Abstract: The substantial heat generation in modern electronic devices is one of the major issues requiring efficient thermal management. This work demonstrates a novel concept for the design of thermally conducting networks inside a polymer matrix for the development of highly thermally conductive composites. Highly ordered hexagonal boron nitride (hBN) structures are obtained utilizing a freeze‐casting method. These structures are then thermally sintered to get a continuous network of BN⊥ –BN⊥ of high thermal conductivity in which a polymer matrix can be impregnated, enabling a directional and thermally conducting composite. The highest achieved thermal conductivity ( K ) is 4.38 W m −1 K −1 with a BN loading of 32 vol%. The effect of sintering temperatures on the K of the composite is investigated to optimize connectivity and thermal pathways while maintaining an open structure (porosity ≈ 2.7%). The composites also maintain good electrical insulation (volume resistivity ≈ 10 14 Ω cm). This new approach of thermally sintering BN⊥ –BN⊥ aligned structures opens up a new avenue for the design and preparation of filler alignment in polymer‐based composites for improving the thermal conductivity while maintaining high electrical resistance, which is a topic of interest in electronic packaging and power electronics applications. Abstract : A new concept in material design by constructing thermal conduction skeletons inside a polymer matrix for the development of thermal conductive composites is demonstrated. Aligned hexagonal boron nitride structures are thermally sintered to get a continuous network with BN⊥ –BN⊥ diffused interfaces in which a polymer resin is impregnated, enabling the formation of directional and highly thermal conductive composites.